Survey of smokers' reasons for not switching to safer sources of nicotine and their willingness to do so in the future - Phillips Carl V; Rosenberg Zale; Heavner Karyn K (BMC, 2009)
Abstract Despite the well-known risks of smoking, policy, social pressure, and accessible cessation programs, tens of millions of North American adults continue smoking rather than quitting or switching to less harmful non-combustion nicotine products. We surveyed people smoking in public in Edmonton, Canada (n = 242, year = 2007) to investigate smokers' reasons for resisting switching to low-risk nicotine sources. 43% had used low-risk products (mostly pharmaceutical nicotine). 75% indicated willingness to consider switching to low-risk products. Smokers cited similar reasons for not switching to smokeless tobacco and pharmaceutical nicotine, largely based on misinformation. Accurate risk information may lead many to try low-risk nicotine products.